Demography and Ecology - B.B.Umarov; R.K.Rahmatov; H.D.Muhammadjonov (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
This article analyzes the relationship between demography and ecology on a scientific and theoretical basis. The pressure on the natural environment of demographic processes such as population growth, urbanization and migration, as well as the negative consequences of environmental problems such as global warming, resource scarcity, and biodiversity loss, are discussed in detail. The article analyzes modern environmental problems in relation to demographic factors, indicating the roots of the problems and ways to eliminate them.